Membrane-deforming Proteins Play Distinct Roles in Actin Pedestal Biogenesis by Enterohemorrhagic Escherichia coli - Campellone, Kenneth G. (American Society for Biochemistry and Molecular Biology, 2012)
Many bacterial pathogens reorganize the host actin cytoskeleton during the course of infection, including enterohemorrhagic Escherichia coli (EHEC), which utilizes the effector protein EspF(U) to assemble actin filaments within plasma membrane protrusions called pedestals. EspF(U) activates N-WASP, a host actin nucleation-promoting factor that is normally auto-inhibited and found in a complex with the actin-binding protein WIP. Under native conditions, this N-WASP/WIP complex is activated by the small GTPase Cdc42 in concert with several different SH3 (Src-homology-3) domain-containing proteins. In the current study, we tested whether SH3 domains from the F-BAR (FCH-Bin-Amphiphysin-Rvs) subfamily of membrane-deforming proteins are involved in actin pedestal formation. We found that three F-BAR proteins: CIP4, FBP17, and TOCA1 (transducer of Cdc42-dependent actin assembly), play different roles during actin pedestal biogenesis. Whereas CIP4 and FBP17 inhibited actin pedestal assembly, TOCA1 stimulated this process. TOCA1 was recruited to pedestals by its SH3 domain, which bound directly to proline-rich sequences within EspF(U). Moreover, EspF(U) and TOCA1 activated the N-WASP/WIP complex in an additive fashion in vitro, suggesting that TOCA1 can augment actin assembly within pedestals. These results reveal that EspF(U) acts as a scaffold to recruit multiple actin assembly factors whose functions are normally regulated by Cdc42.